Modified sodium ion battery positive electrode material and preparation method and application thereof

By using anhydrous oxalic acid as a modification additive in the positive electrode material of sodium ion battery, a stable covalent bond network and surface cladding layer is formed, the problem of positive electrode material being prone to moisture absorption and deterioration in the natural environment is solved, the structural and chemical stability of the material is significantly improved, and the battery cycle life is extended.

CN119612553AActive Publication Date: 2025-03-14ZIBO TORCH ENERGY
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202510152113.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-12
Publication Date
2025-03-14
Estimated Expiration
2045-02-12

AI Technical Summary

Technical Problem

The positive electrode material of sodium ion battery is prone to moisture absorption and deterioration in natural environment, resulting in a decrease in electrochemical performance, limiting its practical application. The existing modification methods have complex processes, high costs or limited modification effects, making it difficult to take into account the electrochemical properties and environmental stability of the materials.

Method used

Anhydrous oxalic acid is used as a modification additive to form a stable covalent bond network and a uniform surface coating layer by hydrothermal method to inhibit the volume expansion of the electrode material and the dissolution of the transition metal, and extend the battery cycle life.

Benefits of technology

It significantly enhances the structural stability and chemical stability of the positive electrode material, inhibits hygroscopic deterioration, ensures the long-lasting and stable battery performance, and provides a high-stability and long-life sodium ion battery material foundation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention belongs to the technical field of sodium batteries, and particularly relates to a modified sodium ion battery positive electrode material and a preparation method and application thereof. The preparation method comprises the following steps: (1) mixing Prussian white with anhydrous oxalic acid, and carrying out dry ball milling under a vacuum condition to obtain mixed powder; (2) adding the mixed powder into a polytetrafluoroethylene-lined reaction kettle filled with ethanol, sealing the reaction kettle, and carrying out hydrothermal reaction in a muffle furnace; and (3) cleaning the powder obtained after the hydrothermal reaction in the step (2) by using a sodium carbonate solution, and after cleaning is completed, carrying out vacuum drying treatment on the powder to obtain the modified sodium ion battery positive electrode material after drying. The anhydrous oxalic acid is adopted as a modification additive, and a stable covalent bond network and a uniform surface coating layer are formed through a hydrothermal method, so that volume expansion and transition metal dissolution of the electrode material in the charging and discharging process can be effectively inhibited, and the cycle life of the battery is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sodium batteries, and in particular relates to a modified sodium ion battery positive electrode material and a preparation method and application thereof. Background Art

[0002] Sodium-ion batteries, as an emerging secondary battery technology, have rapidly become a hot topic in the field of research and application in recent years due to their significant advantages in safety, cost-effectiveness and abundance of raw materials. This type of battery stores and releases electrical energy through the reversible insertion and extraction of sodium ions between the positive and negative electrodes, providing strong support for the large-scale storage of renewable energy and the construction of smart grids. However, the development of sodium-ion batteries still faces some technical challenges, among which the environmental adaptability of the positive electrode material is one of the key issues that needs to be solved urgently.

[0003] At present, the positive electrode materials of sodium ion batteries (such as Prussian white) are very easy to absorb moisture and deteriorate in the natural environment, resulting in a significant decrease in their electrochemical performance, which seriously limits their practical application. The root of this problem is that the positive electrode materials are highly sensitive to humidity, which requires strict environmental control during their preparation, storage and use, increasing production costs and technical difficulties. Therefore, the development of a modified sodium ion battery positive electrode material with strong environmental adaptability has become an important research direction to promote the commercial application of sodium ion battery technology.

[0004] In the prior art, the modification methods for the positive electrode materials of sodium ion batteries mainly include surface coating, element doping and structural optimization. However, these methods often have problems such as complex process, high cost or limited modification effect, and it is difficult to take into account both the electrochemical performance and environmental stability of the materials. Therefore, it is urgent to develop a modification method with simple process, low cost and significant improvement of the environmental adaptability and electrochemical performance of the positive electrode materials to meet the needs of sodium ion batteries in practical applications. Summary of the invention

[0005] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a modified sodium ion battery positive electrode material. By using anhydrous oxalic acid as a modified additive, a stable covalent bond network and a uniform surface coating layer formed by a hydrothermal method can effectively inhibit the volume expansion of the electrode material during the charge and discharge process and the dissolution of transition metals, thereby extending the battery cycle life.

[0006] Another object of the present invention is to provide a preparation method and application of a modified sodium ion battery positive electrode material.

[0007] The technical solution adopted by the present invention is as follows: The method for preparing the modified sodium ion battery positive electrode material comprises the following steps: (1) Prussian white and anhydrous oxalic acid are mixed and dry-milled under vacuum conditions to obtain a mixed powder; (2) adding the mixed powder into a polytetrafluoroethylene-lined reactor filled with ethanol, then sealing the reactor and placing it in a muffle furnace for hydrothermal reaction; (3) The powder obtained after the hydrothermal reaction in step (2) is washed with a sodium carbonate solution. After washing, the powder is vacuum dried to obtain a modified sodium ion battery positive electrode material.

[0008] In the step (1), the mass ratio of Prussian white to anhydrous oxalic acid is 30:(1-3).

[0009] In the step (1), a planetary ball mill is used for dry ball milling, agate balls are used as grinding balls, the rotation speed of the dry ball milling is 150-200 rpm, and the dry ball milling time is 2-3 hours.

[0010] In the step (1), the ball-to-material ratio of dry ball milling is (8-10):1.

[0011] In the step (2), the temperature of the hydrothermal reaction is 200-250°C, the time of the hydrothermal reaction is 6-10h, and the heating rate is 1-3°C / min.

[0012] In the step (2), the mass volume ratio of the mixed powder and the added amount of ethanol is (2-3): 10 mg / mL.

[0013] In the step (3), the concentration of the sodium carbonate solution is 1-3 mol / L.

[0014] In the step (3), the drying temperature is 90-120°C and the drying time is 8-12 hours.

[0015] The modified sodium ion battery positive electrode material is prepared by the above-mentioned method for preparing the modified sodium ion battery positive electrode material.

[0016] The modified sodium ion battery positive electrode material is used to prepare a sodium ion battery.

[0017] Compared with the prior art, the present invention has the following beneficial effects: The preparation method of the modified sodium ion battery positive electrode material of the present invention greatly enhances the structural stability and chemical stability of the prepared positive electrode material by using anhydrous oxalic acid as a modification additive, thereby effectively inhibiting the moisture absorption and deterioration phenomenon in the air environment, and ensuring the long-term stability of the battery performance. In addition, the prepared positive electrode material exhibits excellent electrochemical performance and high gram capacity, providing a solid material foundation and technical support for the development of high-stability and long-life sodium ion batteries. DETAILED DESCRIPTION

[0018] The present invention is further described below with reference to the embodiments, but they do not limit the implementation of the present invention.

[0019] Unless otherwise specified, the raw materials used in the examples and comparative examples are conventional commercially available raw materials, and the process methods used in the examples and comparative examples are conventional methods in the art unless otherwise specified.

[0020] Example 1 The method for preparing the modified sodium ion battery positive electrode material comprises the following steps: (1) Prussian white and anhydrous oxalic acid were mixed in a mass ratio of 30:1, and dry-milled in a planetary ball mill under vacuum conditions. Agate balls were used as grinding balls. The speed of the dry-milling was 150 rpm. The dry-milling time was 2 h. The ball-to-material ratio of the dry-milling was 8:1. After dry-milling, a mixed powder was obtained; (2) adding the mixed powder into a polytetrafluoroethylene-lined reactor filled with ethanol, wherein the mass volume ratio of the mixed powder to the ethanol added is 2:10 mg / mL; then the reactor is sealed and placed in a muffle furnace for a hydrothermal reaction, wherein the temperature of the hydrothermal reaction is 200°C, the time of the hydrothermal reaction is 6 hours, and the heating rate is 1°C / min; (3) The powder obtained after the hydrothermal reaction in step (2) is washed with a sodium carbonate solution with a concentration of 1 mol / L. After washing, the powder is vacuum dried at a temperature of 90° C. for 8 h. After drying, a modified sodium ion battery positive electrode material is obtained.

[0021] Example 2 The method for preparing the modified sodium ion battery positive electrode material comprises the following steps: (1) Prussian white and anhydrous oxalic acid were mixed in a mass ratio of 30:2, and dry-milled in a planetary ball mill under vacuum conditions. Agate balls were used as grinding balls. The speed of the dry-milling was 170 rpm. The dry-milling time was 3 h. The ball-to-material ratio of the dry-milling was 9:1. After dry-milling, a mixed powder was obtained; (2) adding the mixed powder into a polytetrafluoroethylene-lined reactor filled with ethanol, wherein the mass volume ratio of the mixed powder to ethanol added is 3:10 mg / mL; then sealing the reactor and placing it in a muffle furnace for hydrothermal reaction, wherein the temperature of the hydrothermal reaction is 220°C, the time of the hydrothermal reaction is 8 hours, and the heating rate is 2°C / min; (3) The powder obtained after the hydrothermal reaction in step (2) is washed with a sodium carbonate solution with a concentration of 2 mol / L. After washing, the powder is vacuum dried at a temperature of 100° C. for 10 h. After drying, a modified sodium ion battery positive electrode material is obtained.

[0022] Example 3 The method for preparing the modified sodium ion battery positive electrode material comprises the following steps: (1) Prussian white and anhydrous oxalic acid were mixed in a mass ratio of 30:3, and dry-milled in a planetary ball mill under vacuum conditions. Agate balls were used as grinding balls. The speed of the dry-milling was 150 rpm. The dry-milling time was 2 h. The ball-to-material ratio was 9:1. After dry-milling, a mixed powder was obtained. (2) adding the mixed powder into a polytetrafluoroethylene-lined reactor filled with ethanol, wherein the mass volume ratio of the mixed powder to the ethanol added is 2.5:10 mg / mL; then the reactor is sealed and placed in a muffle furnace for a hydrothermal reaction, wherein the temperature of the hydrothermal reaction is 200°C, the time of the hydrothermal reaction is 10 h, and the heating rate is 1°C / min; (3) The powder obtained after the hydrothermal reaction in step (2) is washed with a sodium carbonate solution with a concentration of 3 mol / L. After washing, the powder is vacuum dried at a temperature of 120° C. for 8 h. After drying, a modified sodium ion battery positive electrode material is obtained.

[0023] Example 4 The method for preparing the modified sodium ion battery positive electrode material comprises the following steps: (1) Prussian white and anhydrous oxalic acid were mixed in a mass ratio of 30:2, and dry-milled in a planetary ball mill under vacuum conditions. Agate balls were used as grinding balls. The speed of the dry milling was 200 rpm. The dry milling time was 2 h. The ball-to-material ratio of the dry milling was 10:1. After dry milling, a mixed powder was obtained; (2) adding the mixed powder into a polytetrafluoroethylene-lined reactor filled with ethanol, wherein the mass volume ratio of the mixed powder to ethanol is 2:10 mg / mL; then sealing the reactor and placing it in a muffle furnace for hydrothermal reaction, wherein the temperature of the hydrothermal reaction is 250°C, the time of the hydrothermal reaction is 10 h, and the heating rate is 3°C / min; (3) The powder obtained after the hydrothermal reaction in step (2) is washed with a sodium carbonate solution with a concentration of 1 mol / L. After washing, the powder is vacuum dried at a temperature of 100° C. for 12 h. After drying, a modified sodium ion battery positive electrode material is obtained.

[0024] Example 5 The method for preparing the modified sodium ion battery positive electrode material comprises the following steps: (1) Prussian white and anhydrous oxalic acid were mixed in a mass ratio of 30:1, and dry-milled in a planetary ball mill under vacuum conditions. Agate balls were used as grinding balls. The speed of the dry-milling was 150 rpm. The dry-milling time was 3 h. The ball-to-material ratio of the dry-milling was 10:1. After dry-milling, a mixed powder was obtained; (2) adding the mixed powder into a polytetrafluoroethylene-lined reactor filled with ethanol, wherein the mass volume ratio of the mixed powder to ethanol added is 3:10 mg / mL; then the reactor is sealed and placed in a muffle furnace for hydrothermal reaction, wherein the temperature of the hydrothermal reaction is 220°C, the time of the hydrothermal reaction is 6 hours, and the heating rate is 2°C / min; (3) The powder obtained after the hydrothermal reaction in step (2) is washed with a sodium carbonate solution with a concentration of 2 mol / L. After washing, the powder is vacuum dried at a temperature of 120° C. for 10 h. After drying, a modified sodium ion battery positive electrode material is obtained.

[0025] Comparative Example 1 The difference from Example 1 is that anhydrous oxalic acid is not added in step (1).

[0026] Comparative Example 2 The difference from Example 2 is that the step (2) is to place the mixed powder into a vacuum drying oven, and under vacuum conditions, heat the mixture to 220° C. at a rate of 2° C. / min for 8 h.

[0027] The positive electrode materials prepared in Examples 1-5 and Comparative Examples 1-2 were respectively used to assemble CR2032 button batteries and soft-pack sodium ion batteries, as follows: The assembly process of CR2032 button battery is as follows: The positive electrode materials prepared in Examples 1-5 and Comparative Examples 1-2 were used as the positive electrode, the sodium sheet was used as the negative electrode, and a 290 μm thick GF / A glass fiber separator was used; NaPF6 was used as the solute, and a mixture of EC, DMC and DEC in a volume ratio of 1:1:1 was used as the solvent. A NaPF6 solution with a concentration of 1 mol / L was prepared as the electrolyte, and a CR2032 button battery was assembled. After the assembly was completed, it was allowed to stand for 12 hours, and at a current density of 0.1C, it was charged to 4.0V, and then discharged to 1.5V, and the gram capacity (mAh / g) of the CR2032 button battery was tested.

[0028] The assembly process of soft-pack sodium-ion batteries is: The positive electrode materials prepared in Examples 1-5 and Comparative Examples 1-2 were used as the positive electrode, and hard carbon was used as the negative electrode to prepare positive electrode sheets of 96 mm×81 mm and negative electrode sheets of 98 mm×83 mm, respectively; NaPF6 was used as the solute and a mixture of EC, DMC and DEC in a volume ratio of 1:1:1 was used as the solvent to prepare a NaPF6 solution with a concentration of 1 mol / L as the electrolyte; a soft-pack sodium ion battery was assembled using a ceramic diaphragm with an NP ratio of 1.1:1; after assembly, the battery was allowed to stand for 12 hours, and at a current density of 1C, the battery was charged to 4.0 V and then discharged to 1.5 V as one charge and discharge cycle, and the capacity retention rate (%) of the soft-pack sodium ion battery after 50 charge and discharge cycles was tested, and the appearance of the soft-pack sodium ion battery after 50 charge and discharge cycles was observed.

[0029] The test data is shown in Table 1.

[0030] Table 1 Performance test results

[0031] It can be seen from the data in Table 1 that the CR2032 button battery assembled with the positive electrode material prepared in Examples 1-5 has a higher gram capacity, and the capacity retention rate of the soft-pack sodium ion battery assembled with the positive electrode material prepared in Examples 1-5 is above 97% after 50 charge and discharge cycles, and there is no obvious bloating phenomenon in the appearance of the soft-pack sodium ion battery after 50 charge and discharge cycles.

[0032] Compared with Example 1, since no anhydrous oxalic acid was added in Comparative Example 1, the gram capacity of the CR2032 button battery assembled with the positive electrode material of Comparative Example 1 was significantly lower than that of Example 1. The soft-pack sodium ion battery assembled with the positive electrode material of Comparative Example 1 had obvious flatulence after 50 cycles of charge and discharge at a current density of 1C, and the capacity retention rate after 50 cycles of charge and discharge was lower than that of Example 1. The main reason for this phenomenon is that the addition of anhydrous oxalic acid played a key role in Example 1: oxalate formed a complex with the transition metal in Prussian white, inhibiting the formation of the cubic structure of Prussian white, thereby reducing the possibility of water molecules entering the vacancies of the cubic structure and avoiding the formation of Prussian white with crystal water. Therefore, the positive electrode material in Example 1 showed higher structural stability and electrochemical performance in the electrochemical reaction. However, due to the lack of this effect of anhydrous oxalic acid in Comparative Example 1, the material structure was unstable, and side reactions were more likely to occur and gas was generated during the cycle, thereby causing obvious flatulence.

[0033] Compared with Example 2, in Comparative Example 2, since no hydrothermal reaction was performed in step (2), but a direct vacuum heating method was used for the reaction, the gram capacity of the CR2032 button battery assembled with the positive electrode material of Comparative Example 2 was lower than that of Example 2, and the capacity retention rate of the soft-pack sodium ion battery assembled with the positive electrode material of Comparative Example 2 after 50 charge and discharge cycles was also lower than that of Example 2. This is because the hydrothermal method can provide a high-pressure environment, which promotes oxalate and the transition metal in Prussian white to form a stable covalent bond more effectively, thereby optimizing the structure and electrochemical properties of the material. However, due to the lack of high-pressure conditions, the direct vacuum heating method has a low efficiency in combining oxalate and transition metals, resulting in poor structural integrity of the material, which in turn affects the overall performance of the battery.

Claims

1. A method for preparing a modified sodium ion battery positive electrode material, characterized in that: The following steps are involved: (1) Prussian white and anhydrous oxalic acid are mixed and dry-milled under vacuum conditions to obtain a mixed powder; (2) adding the mixed powder into a polytetrafluoroethylene-lined reactor filled with ethanol, then sealing the reactor and placing it in a muffle furnace for hydrothermal reaction; (3) The powder obtained after the hydrothermal reaction in step (2) is washed with a sodium carbonate solution. After washing, the powder is vacuum dried to obtain a modified sodium ion battery positive electrode material.

2. The method for preparing the modified sodium ion battery positive electrode material according to claim 1, characterized in that: In the step (1), the mass ratio of Prussian white to anhydrous oxalic acid is 30:(1-3).

3. The method for preparing the modified sodium ion battery positive electrode material according to claim 1, characterized in that: In the step (1), the rotation speed of the dry ball milling is 150-200 rpm, and the time of the dry ball milling is 2-3 hours.

4. The method for preparing the modified sodium ion battery positive electrode material according to claim 1, characterized in that: In the step (1), the ball-to-material ratio of dry ball milling is (8-10):

1.

5. The method for preparing the modified sodium ion battery positive electrode material according to claim 1, characterized in that: In the step (2), the temperature of the hydrothermal reaction is 200-250°C, the time of the hydrothermal reaction is 6-10h, and the heating rate is 1-3°C / min.

6. The method for preparing the modified sodium ion battery positive electrode material according to claim 1, characterized in that: In the step (2), the mass volume ratio of the mixed powder and the added amount of ethanol is (2-3): 10 mg / mL.

7. The method for preparing a modified sodium ion battery positive electrode material according to claim 1, characterized in that: In the step (3), the concentration of the sodium carbonate solution is 1-3 mol / L.

8. The method for preparing the modified sodium ion battery positive electrode material according to claim 1, characterized in that: In the step (3), the drying temperature is 90-120°C and the drying time is 8-12 hours.

9. A modified sodium ion battery positive electrode material, characterized in that: The modified sodium ion battery positive electrode material is prepared by the preparation method of any one of claims 1 to 8.

10. An application of the modified sodium ion battery positive electrode material according to claim 9, characterized in that: Used in the preparation of sodium ion batteries.

Citation Information

Patent Citations

  • Preparation method of Prussian blue based sodium ion battery positive electrode material

    CN106654263A

  • Carbon-coated transition metal oxide based on prussian blue analogue as well as preparation method and application of carbon-coated transition metal oxide

    CN112151804A

  • Preparation method and application of Prussian blue sodium ion battery positive electrode material

    CN115611296A

  • Preparation method and application of Prussian blue material with high thermal stability

    CN116216746A

  • Positive plate processing technology of sodium ion battery and positive plate

    CN116722105A